(untitled) (Western European Journal of Historical Events and Social Science, 2025)
This article explores the philosophical and psychological dimensions of the works of Mirza Abdulqadir Bedil (1642–1720), one of the greatest representatives of Indo-Persian mystical literature. By interpreting Bedil’s views through the lens of personality psychology, the study highlights his understanding of the human inner world — the dynamics of conflict, transformation, and harmony. Bedil’s philosophy is shown to anticipate many modern psychological theories concerning the struggle between reason and passion, the process of individuation, and the realization of the “true self.” His concept of inner balance is compared to humanistic and existential approaches in psychology, particularly those of Freud, Jung, and Maslow. The article concludes that Bedil’s synthesis of mystical intuition and rational reflection forms a unique psychological model of self-awareness and inner harmony, relevant to the moral and mental development of modern humanity.